Water for food security, nutrition and social justice - Mehta, Lyla; Oweis, Theib; Ringler, Claudia; Schreiner, Barbara; Varghese, Shiney (Routledge, 2019)
In many slums and informal settlements in the global South, the quality of water accessed by poor people is so bad that it adversely affects health and nutrition, especially of children and babies. Moreover, many of these settlements lack adequate sanitation, which contributes to disease, such as diarrhoea, which further contributes to poor nutritional outcomes. Safe drinking water and sanitation are fundamental to the nutrition, health and dignity of all. Despite the progress made in achieving global targets around water and sanitation, about 3 in 10 people, or 2.1 billion lack access to safe, readily available water at home, and 6 in 10, or 4.5 billion, lack safely managed sanitation. Growing water scarcity and variability will increase the competition for water resources across sectors, with water often being taken away from the agricultural sector to drive greater economic value per unit of water in other sectors. The chapter also presents an overview of the key concepts discussed in this book.